RhoA/ROCK signalling activated by ARHGEF3 promotes muscle weakness via autophagy in dystrophic mdx mice - Jae‐Sung You; Yongdeok Kim; Soohyun Lee; Rashid Bashir; Jie Chen (Wiley, 2023)
Abstract Background Duchenne muscular dystrophy (DMD), caused by dystrophin deficiency, leads to progressive and fatal muscle weakness through yet‐to‐be‐fully deciphered molecular perturbations. Emerging evidence implicates RhoA/Rho‐associated protein kinase (ROCK) signalling in DMD pathology, yet its direct role in DMD muscle function, and related mechanisms, are unknown. Methods Three‐dimensionally engineered dystrophin‐deficient mdx skeletal muscles and mdx mice were used to test the role of ROCK in DMD muscle function in vitro and in situ, respectively. The role of ARHGEF3, one of the RhoA guanine nucleotide exchange factors (GEFs), in RhoA/ROCK signalling and DMD pathology was examined by generating Arhgef3 knockout mdx mice. The role of RhoA/ROCK signalling in mediating the function of ARHGEF3 was determined by evaluating the effects of wild‐type or GEF‐inactive ARHGEF3 overexpression with ROCK inhibitor treatment. To gain more mechanistic insights, autophagy flux and the role of autophagy were assessed in various conditions with chloroquine. Results Inhibition of ROCK with Y‐27632 improved muscle force production in 3D‐engineered mdx muscles (+25% from three independent experiments, P < 0.05) and in mice (+25%, P < 0.001). Unlike suggested by previous studies, this improvement was independent of muscle differentiation or quantity and instead related to increased muscle quality. We found that ARHGEF3 was elevated and responsible for RhoA/ROCK activation in mdx muscles, and that depleting ARHGEF3 in mdx mice restored muscle quality (up to +36%, P < 0.01) and morphology without affecting regeneration. Conversely, overexpressing ARHGEF3 further compromised mdx muscle quality (−13% vs. empty vector control, P < 0.01) in GEF activity‐ and ROCK‐dependent manner. Notably, ARHGEF3/ROCK inhibition exerted the effects by rescuing autophagy which is commonly impaired in dystrophic muscles. Conclusions Our findings uncover a new pathological mechanism of muscle weakness in DMD involving the ARHGEF3‐ROCK‐autophagy pathway and the therapeutic potential of targeting ARHGEF3 in DMD.